2019
DOI: 10.1101/777227
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome wide DNA methylation profiling identifies specific epigenetic features in high-risk cutaneous squamous cell carcinoma

Abstract: Cutaneous squamous cell carcinoma (cSCC) is the second most common skin cancer. Although most cSCCs have good prognosis, a subgroup of high-risk cSCC has a higher frequency of recurrence and mortality. Therefore, the identification of molecular risk factors associated with this aggressive subtype is of major interest. In this work we carried out a global-scale approach to investigate the DNA-methylation profile in patients at different stages, from premalignant actinic keratosis to lowrisk invasive and high-ri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…In cutaneous melanoma, it was demonstrated that promoter hypomethylation and intragenic hypermethylation of specific genes are associated with tumor aggressiveness due to the alteration of extracellular matrix components and the upregulation of matrix metalloproteinases [ 98 , 99 , 100 ]. This highlights the clinical potential of deregulated methylation status as a hallmark for carcinogenesis, allowing the recognition of various methylation patterns as biomarkers for diagnosis and prognosis [ 101 ] ( Table 1 ). Methylation studies focusing on cSCC, have demonstrated various patterns.…”
Section: Current Molecular Biomarkers For Nmscmentioning
confidence: 99%
See 1 more Smart Citation
“…In cutaneous melanoma, it was demonstrated that promoter hypomethylation and intragenic hypermethylation of specific genes are associated with tumor aggressiveness due to the alteration of extracellular matrix components and the upregulation of matrix metalloproteinases [ 98 , 99 , 100 ]. This highlights the clinical potential of deregulated methylation status as a hallmark for carcinogenesis, allowing the recognition of various methylation patterns as biomarkers for diagnosis and prognosis [ 101 ] ( Table 1 ). Methylation studies focusing on cSCC, have demonstrated various patterns.…”
Section: Current Molecular Biomarkers For Nmscmentioning
confidence: 99%
“…In detail, they demonstrated a differential methylation status between the two pathological stages, with low-risk SCCs being hypomethylated and high-risk SCCs hypermethylated. According to the authors, this finding may suggest a sequential approach of SCC formation, where UV-exposure leads to hypomethylation and thus foretells the premalignant and low-risk stages of cSCC, while advanced stages of SCC present a hypermethylated status [ 101 ]. As regards the evaluation of the methylation status of BCC, Goldberg et al presented the FHIT promoter to be hypomethylated [ 114 ], while Heitzer et al found the hypermethylated PTCH promoter only in a small number of cases [ 115 ].…”
Section: Current Molecular Biomarkers For Nmscmentioning
confidence: 99%
“…Methylation of DNA is an epigenetic change that can alter expression of genes that has been linked to many cancers including cSCC (19)(20)(21). Several DNA tumour viruses such as EBV, HBV and HPV have been found to dysregulate host gene DNA methylation (22).…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic epithelial-mesenchymal crosstalk characteristic of hair follicle stem cells (HFSc) from embryonic development to adulthood can be found during normal hair follicle growth and cyclic regeneration [7]. Interestingly, emerging studies have revealed important functions of DNA methylation in skin biology such as it can regulate HFSc differentiation [8,9]. DNA methylation is an epigenetic modification to change the epigenome that was mediated by DNA methyltransferase (DNMT).…”
Section: Introductionmentioning
confidence: 99%